A Dual Case of Peritonitis and Central Nervous System Infection Caused by Nutritionally Variant Streptococcal Species - Sussi Vivar; Jennifer E. Girotto; Thomas S. Murray (Case Reports in Infectious Diseases)
Nutritional variant streptococci (NVS) are difficult to identify bacteria that can cause invasive infections such as endocarditis and meningitis. NVS as a cause of peritonitis has not been routinely described. This case of NVS as the etiology of peritonitis associated with previous neurosurgery and ventriculoperitoneal (VP) shunt revision demonstrates its potential role as a significant pathogen in patients with peritonitis and VP shunts. Therapy consists of vancomycin plus a second agent but since there are no standards for susceptibility testing, clinical response remains the standard for determining the efficacy of treatment. When there is central nervous system (CNS) involvement it is important to include drugs with appropriate CNS penetration.